1982
DOI: 10.1901/jeab.1982.38-19
|View full text |Cite
|
Sign up to set email alerts
|

Schedule‐induced Defecation

Abstract: Excessive defecation, typically considered to be a concomitant of stress, was experimentally induced or eliminated under specific schedules of positive reinforcement of lever pressing by rats. The schedules were, by and large, those under which polydipsia is typically induced. In the first of three experiments, rats under fixed-interval 32-second schedules and variable interval 32-second schedules for food and water reinforcers defecated profusely, but not under fixed-interval one-second schedules or other sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

1986
1986
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
0
5
0
2
Order By: Relevance
“…In 1961, Falk observed that exposure of food-deprived rats to intermittent food reinforcement schedules, with free access to a bottle containing water in the experimental chambers, caused the development of excessive drinking (schedule-induced polydipsia, SIP) unrelated to physiological needs or apparent behavior regulation. Other similar behavioral patterns were later studied, such as wheel running (Levitsky & Collier, 1968), air licking (Mendelson & Chillag, 1970), wood chewing (Roper & Crossland, 1982), pica (Villareal, 1967), aggression (Looney & Cohen, 1982), escape (Brown & Flory, 1972), defecation (Rayfield, Segal & Goldiamond, 1982) and a long list of other activities (see reviews by Falk, 1977;Pellón, 1990), all in theory being modulated by the degree of intermittency in the reinforcement. These behavioral patterns have been called adjunctive behaviors (or schedule-induced behaviors) (Falk, 1971;Roper & Posadas-Andrews, 1981;Staddon, 1977;Timberlake, Wahl & King, 1982;Wetherington, 1982), and are characterized primarily by meeting the criteria of significantly higher response rates when exposed to intermittent reinforcement (albeit without an explicitly arranged contingency between behavior and reinforcer occurrence) which are usually observed following the reinforcer in the form of an inverted-U throughout the inter-reinforcement interval.…”
Section: Universidad Nacional De Educación a Distancia (Uned) Spainmentioning
confidence: 99%
“…In 1961, Falk observed that exposure of food-deprived rats to intermittent food reinforcement schedules, with free access to a bottle containing water in the experimental chambers, caused the development of excessive drinking (schedule-induced polydipsia, SIP) unrelated to physiological needs or apparent behavior regulation. Other similar behavioral patterns were later studied, such as wheel running (Levitsky & Collier, 1968), air licking (Mendelson & Chillag, 1970), wood chewing (Roper & Crossland, 1982), pica (Villareal, 1967), aggression (Looney & Cohen, 1982), escape (Brown & Flory, 1972), defecation (Rayfield, Segal & Goldiamond, 1982) and a long list of other activities (see reviews by Falk, 1977;Pellón, 1990), all in theory being modulated by the degree of intermittency in the reinforcement. These behavioral patterns have been called adjunctive behaviors (or schedule-induced behaviors) (Falk, 1971;Roper & Posadas-Andrews, 1981;Staddon, 1977;Timberlake, Wahl & King, 1982;Wetherington, 1982), and are characterized primarily by meeting the criteria of significantly higher response rates when exposed to intermittent reinforcement (albeit without an explicitly arranged contingency between behavior and reinforcer occurrence) which are usually observed following the reinforcer in the form of an inverted-U throughout the inter-reinforcement interval.…”
Section: Universidad Nacional De Educación a Distancia (Uned) Spainmentioning
confidence: 99%
“…In addition to rats, schedule-induced polydipsia also develops in mice (Palfai, Kutscher, & Symons, 1971), guinea pigs (Porter, Sozer, & Moeschl, 1977), gerbils (Porter & Bryant, 1978), and rhesus monkeys (Allen & Kenshalo, 1976). Other induced or adjunctive patterns of behavior have been observed, including aggression in pigeons (Looney & Cohen, 1982, for a review), defecation in rats (Rayfield, Segal, & Goldiamond, 1982), and the ingestion of nonnutritive substances in monkeys (Villareal, 1967). Schedule-induced polydipsia and other adjunctive behavior have received much empirical and theoretical attention (see reviews by Falk, 1977;Staddon, 1977;Wetherington, 1982), but our understanding of these phenomena is still incomplete (see Reid & Staddon, 1990).…”
mentioning
confidence: 99%
“…For example intermittent (60 s) pellet presentations in an operant chamber to food-deprived rats, whether response independent (Fixed Time) or response dependent (Fixed Interval), generate several classes of excessive behavior that have been labeled “schedule-induced” or “adjunctive”. Some of the earliest identified classes of behaviors included polydipsia, [28], air-licking [29] wheel running [30,31], wood chewing [32], and defecation [33] among others. This literature is large and several interpretations have been presented to account for the occurrences of excessive behaviors in the context in which they occur, but without any resolution [34,35].…”
Section: Main Discussionmentioning
confidence: 99%